2018
DOI: 10.1007/s40267-018-0572-5
|View full text |Cite|
|
Sign up to set email alerts
|

Anakinra in Still’s disease: a profile of its use

Abstract: The EU indication for anakinra has been extended to include Still’s disease, a serious rare inflammatory disorder of unknown aetiology that comprises adult-onset Still’s disease (AOSD) and systemic juvenile idiopathic arthritis (SJIA). As activated interleukin-1 pathways are associated with the systemic manifestations of these disorders, targeted treatment with anakinra, an interleukin-1 inhibitor, has been investigated. Across clinical and real-world studies in patients with AOSD and SJIA, treatment with anak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
10
0
2
Order By: Relevance
“…Data reported in this study revealed the similar effectiveness of ANA in sJIA and AOSD, though it remains controversial whether sJIA and AOSD could be considered as an identical disease. However, based on these successful results, many experts contemplate these two entities as a continuum of one only disorder affecting different onset ages (Hayem, 2009; Nirmala et al, 2015; Junge et al, 2017; Lyseng-Williamson, 2018; Martini et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data reported in this study revealed the similar effectiveness of ANA in sJIA and AOSD, though it remains controversial whether sJIA and AOSD could be considered as an identical disease. However, based on these successful results, many experts contemplate these two entities as a continuum of one only disorder affecting different onset ages (Hayem, 2009; Nirmala et al, 2015; Junge et al, 2017; Lyseng-Williamson, 2018; Martini et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic juvenile idiopathic arthritis (sJIA) and adult-onset Still disease (AOSD) represent two multifactorial nonhereditary autoinflammatory disorders related to pediatric and adult patients, respectively, characterized by a defective control of innate immunity, as depicted for hereditary autoinflammatory disorders, and by daily high spiking fevers along with systemic features including serositis, evanescent rash, generalized lymphoadenopathy, and arthritis (Caso et al, 2014; Cimaz, 2016; Rigante, 2017; Giacomelli et al, 2018; Lyseng-Williamson, 2018). These two conditions are accompanied by a relevant risk of mortality (Priori et al, 2010; Kimura et al, 2013; Minoia et al, 2014; Kumar, 2016; Giacomelli et al, 2018), making a timely diagnosis as well as a prompt treatment mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…Anakinra is an IL-1 biological treatment that has been approved in the EU for the treatment of FMF (Table 1). Discussion of the use of anakinra in other approved indications, such as rheumatoid arthritis (RA) [7,8], cryopyrin-associated periodic syndromes (CAPS) and Still's disease [9], is outside the scope of this review.…”
Section: What Is the Rationale For Using Anakinra In Familial Meditermentioning
confidence: 99%
“…Previously, first‐line treatment of sJIA consisted of NSAIDs and long‐term systemic high‐dose glucocorticoids but was undesirable due to its well‐known side effects 13,44 . Recently, a biological disease modifying anti‐rheumatic drug (DMARD) in the form of a specific IL‐1 antagonist anakinra was approved for first‐line treatment in sJIA patients and is known to achieve meaningful response in >50% of sJIA patients within 3 months of treatment, if started in an early phase of the disease 1,11,45 . Treatment of sJIA with DMARDs results in a good prognosis.…”
Section: Discussionmentioning
confidence: 99%